THE EFFECT OF SLEEP QUALITY ON EXECUTIVE FUNCTIONS AND ITS REVIEW ACCORDING TO ISLAMIC VIEWS - Hikmah, Cantikha Nur; Nurhidayati, Ida Ratna (HEARTY, 2026)
This study aims to understand human executive function and the influence of sleep quality on executive function, as well as its role in daily life, according to Islamic perspectives. This research was conducted using an observational analytical method, which examines the relationship between the independent variable (sleep quality) and the dependent variable (executive function). The sample in this study were students from the Faculty of Medicine, Universitas Yarsi, graduating in 2023 and 2024. The results indicate that there are several stress triggers for students, including personal and social factors, lifestyle and culture, and factors arising from academic pressure. Students who have difficulty managing stress will experience increased tension, making it difficult to initiate sleep. The results showed that sleep quality did not have a significant relationship with the Trail Making Test B (TMT B) variable. It can be concluded that poor sleep quality does not necessarily mean poor executive function.